1. The boolean expression $X=B+A\overline{B}+AB$ is equivalent to
- A+B
- $\overline{A}B$
- $\overline{A+B}$
- AB
2. The Boolean expression X = (A + B)(C + D) represents
- two ORs ANDed together
- two ANDs ORed together
- A 4-input AND gate
- a 4-input OR gate
3. Which of the following boolean expressions is ‘NOT TRUE’?
- A + 1 = A
- $A + \overline{A}=1$
- A.A = A
- $A.\overline{A}=0$
4. The complement form of $A(B+C)(\overline{C}+\overline{D})$ is
- $A + \overline{B}\,\overline{C}+\overline{D}C=1$
- A +BC + CD
- A + BC
- $\overline{A} + \overline{B}\,\overline{C}+CD$
5. The simplified form of the boolean expression $\overline{A} + A\overline{B}$ is
- A + B
- $A +\overline{B}$
- $\overline{B} + A$
- $\overline{A} + \overline{B}$
6. If A and B are boolean variables, then what is $(A + B).( A + \overline{B})$ is
- B
- A
- A + B
- AB
7. What is the boolean expression A ⊕ B equivalent to?
- $AB+ \overline{A}\,\overline{B}$
- $\overline{A}B + A\overline{B}$
- B
- $\overline{A}$
8. If x and y are boolean variables, which one of the following is the equivalent of x ⊕ y ⊕ xy equivalent to?
- $x+\overline{y}$
- x + y
- 0
- 1
9. Which of the following boolean algebra rules is correct?
- $A.\overline{A}=1$
- A + AB = A + B
- $A + \overline{A}B = A + B$
- A(A+B) = B
10. The simplified logic form of a logic function
$Y=\overline{(\overline{A\overline{B}})(\overline{\overline{A}B})}$
- A + B
- AB
- $\overline{A}+\overline{B}$
- $\overline{A}B + A\overline{B}$
11. The boolean expression $Y=AB+ (A+B)(\overline{A}+B)$ may be simplified as
- Y = A
- $Y = \overline{A}$
- Y = B
- $Y = \overline{B}$
12. The reduced form of the boolean expression
$A[B+C(\overline{AB + AC})]$ is
- $\overline{A}B$
- $A\overline{B}$
- AB
- $AB+B\overline{C}$
13. Which one of the following statements is not correct?
- $X+\overline{X}Y = X$
- $X(\overline{X}+Y) = XY$
- $XY + \overline{X}\,\overline{Y} = X$
- $ZX + Z\overline{X}Y = ZX + ZY$
14. In boolean algebra, if $F = (A+B)(\overline{A}+C)$ then
- $F = AB + \overline{A}C$
- $F = AB + \overline{A}\,\overline{B}$
- $F = AC + \overline{A}B$
- $F = A\overline{A}+\overline{A}B$
15. The expression $(X+Y)(X+\overline{Y})(\overline{X}+Y)$ is equivalent to
- $\overline{X}\,\overline{Y}$
- $\overline{X}Y$
- $X\overline{Y}$
- XY